Association Between Hemoglobin and Elevation Among School-Aged Children: A Verification of Proposed Adjustments. (29th May 2020) - Kanu, Florence; Sharma, Andrea; Addo, O Yaw; Suchdev, Parminder
Abstract: Objectives: Anemia is defined by hemoglobin (Hb) lower than normal based on cutoffs specific to age and sex. Hb increases with elevation as a response to lower blood oxygen, thus adjusting Hb for elevation is necessary before applying cutoffs. Recent evidence among preschool-aged children (PSC) and reproductive-aged women (WRA) suggests current World Health Organization (WHO) recommended Hb elevation adjustments need updating. We examined the Hb and elevation association among school-age children (SAC) to confirm these findings. Methods: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) project data include SAC aged 5–14 years (n = 23, 454; 53.5% female) with data on Hb and elevation (−6 to 3, 834 meters, m) from 6 population-based surveys from 5 countries (Columbia, Ecuador, Malawi, Mexico, United Kingdom). Anemia was defined as Hb < 115 g/L for SAC < 12 years and < 120 g/L for SAC 12–14 years after elevation adjustments. Generalized linear models were used to assess the association between Hb and elevation, including controlling for inflammation-corrected iron and vitamin A deficiency. Hb adjustments for each 500 m increase in elevation from sea level are proposed and compared to current WHO recommendations and new proposed PSC and WRA adjustments. Results: Hb was positively associated with elevation. There was no sex interaction, and the association was robust to model specification. The association among SAC and the resulting Hb adjustments were consistent with PSC and WRA findings, suggesting current WHO recommendations may under-adjust Hb at lower elevation (500–2500 m) and over-adjust Hb at higher elevation (>3000 m). Anemia prevalence in SAC using new elevation adjustments increased by 0.7 (UK) to 14.1 (Malawi) percentage points relative to current WHO elevation adjustments. Conclusions: Results confirm current WHO recommended Hb elevation adjustments may need updating, and anemia prevalence in SAC may be higher than currently estimated. Findings will inform global guidelines on use of elevation-adjusted Hb for anemia assessment and possible need for intervention among SAC. Funding Sources: Bill & Melinda Gates Foundation, Centers for Disease Control and Prevention, Eunice Kennedy Shriver National Institute of Child Health and Human Development, HarvestPlus, and United States Agency for International Development.